(untitled) (FULafia Journal of Science and Technology, 2024)
Salmonella typhi (S. typhi) is a common cause of morbidity and mortality in developing countries. Studies on phenotypic detection of plasmid from ciprofloxacin resistant S. typhi isolated from stool of new students Nasarawa State University, Keffi, was carried out. A total of 180 stool samples were collected from the new students. 30 stool samples were collected from each of the six respective Faculties. 29(16.1%) Salmonella isolates were recovered and identified by standard Microbiological methods. 21(72.4%) of the isolates were Salmonella typhi and 8(27.6%) were Salmonella enteritidis. The prevalence of Salmonella typhi isolation with respect to Faculties was highest in the Faculties of Art (ART) and Law (LAW) with 6(28.6%) isolates each. On the basis of gender, 15 samples each were collected from both male and female students respectively and the highest prevalence of isolation was 4(8.0%) amongst males in the Faculty of LAW and females in the Faculty of ART, while the least prevalence of isolation was zero (0) amongst males in the Faculty of NAT. On the bases of age, the prevalence of isolation was highest amongst the age group 21-30, 19(10.5%), while age group 51-60 showed zero (0) prevalence of isolation. Antimicrobial Susceptibility was carried out using CLSI method; and 21(72.4%) Salmonella typhi isolates were susceptible to Ciprofloxacin, while 8(27.6%) were resistant and the antimicrobial resistance phenotypic pattern of the isolates was also determined. The ciprofloxacin resistance isolates were subjected to “Curing Method” to determine if the resistance was plasmid-mediated or not.